Modelling Australian Transaction Reports and Analysis Centre (AUSTRAC) for Indonesia in Order to Combat Financial Crime - Beny Saputra (NEGREI: Academic Journal of Law and Governance, 2021)
Financial technology (FinTech) rapidly expanding in Indonesia, fund manager around the world eager to invest and diversify their portofolio in this new business strategy, this is due to the fact that Indonesia is the largest economy in the South East Asian (ASEAN) region as well as the 4th most populated country in the planet. As a result this make the market for financial technology in Indonesia has enormous potential  in the future. However, because financial crime is a threat, Indonesia must enchancing their Anti Money laundry (AML) laws for being more practical and adaptable to the current situation. This paper will do doctrinal legal research to analyze effectiveness current law applicable to fight againts money launderer in Indonesia and  comparative law system with modelling AUSTRAC from the Australia which have similar issue with Indonesia. In this respect, data suggest Indonesia in condition almost rechtvaccum for financial tehcnology law and AUSTRAC system in Australia most likely sufficient to implement in Indonesia in order combat money launderer